Downbeat nystagmus: aetiology and comorbidity in 117 patients. Issue 6 (14th September 2007) - Wagner, J N; Glaser, M; Brandt, T; Strupp, M
Abstract : Objectives: Downbeat nystagmus (DBN) is the most common form of acquired involuntary ocular oscillation overriding fixation. According to previous studies, the cause of DBN is unsolved in up to 44% of cases. We reviewed 117 patients to establish whether analysis of a large collective and improved diagnostic means would reduce the number of cases with "idiopathic DBN" and thus change the aetiological spectrum. Methods: The medical records of all patients diagnosed with DBN in our Neurological Dizziness Unit between 1992 and 2006 were reviewed. In the final analysis, only those with documented cranial MRI were included. Their workup comprised a detailed history, standardised neurological, neuro-otological and neuro-ophthalmological examination, and further laboratory tests. Results: In 62% (n = 72) of patients the aetiology was identified ("secondary DBN"), the most frequent causes being cerebellar degeneration (n = 23) and cerebellar ischaemia (n = 10). In 38% (n = 45), no cause was found ("idiopathic DBN"). A major finding was the high comorbidity of both idiopathic and secondary DBN with bilateral vestibulopathy (36%) and the association with polyneuropathy and cerebellar ataxia even without cerebellar pathology on MRI. Conclusions: Idiopathic DBN remains common despite improved diagnostic techniques. Our findings allow the classification of "idiopathic DBN" into three subgroups: "pure" DBN (n = 17); "cerebellar" DBN (ie, DBN plus further cerebellar signs in the absence of cerebellar pathology on MRI; n = 6); and a "syndromatic" form of DBN associated with at least two of the following: bilateral vestibulopathy, cerebellar signs and peripheral neuropathy (n = 16). The latter may be caused by multisystem neurodegeneration.